O-016 Surpass embolization of intracranial aneurysms at two high volume comprehensive stroke centers: unexpectedly high rate of neurologic complications. (4th August 2020) - Roychowdhury, S; Kane, I; Saifuddin, A; Khandelwal, P; Nourallah-Zadeh, E; Gupta, G
Abstract : Introduction/Purpose: The Surpass flow-diverter (FD) has been offered as a new alternative to preexisting Pipeline FD with a comparable safety profile. i Prior publications have listed neurologic morbidity and mortality complication rates as 6% and 2.7% for the Surpass FD & 8.4% & 3.8% for the Pipeline FD respectively. 1, 2, 3 Anecdotal national experiences with the Surpass FD have been mixed, and there is a scarcity of data on real world complications of Surpass FD. A systematic review of cases performed at a high volume comprehensive stroke center involving the Surpass device was conducted. Materials and Methods: A review of all aneurysms treated with the Surpass FD at two high volume aneurysm treatment centers was conducted. Procedures involving the Surpass FD were conducted almost exclusively by experienced neuro-interventionalists with a combined experience of greater than 400 Pipeline FDs at two large academic comprehensive stroke centers. Results: All consecutive cases done between 1/10/2019 to 1/2/2020 were included. There were 55 patients with 68 treated aneurysms. Procedure related complications occurred in 12 patients (21.8% of cases) with permanent neurologic morbidity present in 11 patients (20.0%). Mortality attributable to complications from Surpass stenting occurred in 2 patients (3.6%). Ophthalmologic thromboembolic complications consisting of visual field compromise, ophthalmic artery thrombosis, or retinal hemorrhage occurred in 4 patients (7.3%). Stent thrombosis occurred in 2 cases (3.6%). Technical difficulty in device deployment resulted in 3 complications (5.5%): confirmed distal MCA guidewire perforation; suspected distal MCA guidewire perforation as a cause of immediate post-procedural subarachnoid hemorrhage; and proximal internal carotid artery dissection resulting in ischemic stroke. In one case the Surpass device could not initially be deployed but procedure was repeated later with a proctor present. Seizures developed following the procedure in 5 patients, with focus identified on ipsilateral side in 3 cases & no definitive focus identified in 1 case (7.3% combined attributable cases). Conclusion: Complication rates in addition to technical issues in deployment with the Surpass FD were higher than anticipated, even when performed by experienced neuro-interventionalists. The types of the complications included technical difficulty in device deployment, vascular injury, thromboembolic events and unexplained ipsilateral seizures. Large scale future registry analysis should focus on national data regarding the safety profile of Surpass. References: Wakhloo AK, et al. Surpass flow diverter in the treatment of intracranial aneurysms: a prospective multicenter study. AJNR Am J Neuroradiol 2015 Jan;36(1):98–107. Kallmes DF, et al. International retrospective study of the pipeline embolization device: a multicenter aneurysm treatment study. AJNR Am J Neuroradiol 2015 Jan;36(1):108–115. Park MS, et al. Pipeline embolization device with or without adjunctive coil embolization: analysis of complications from intrePED registry. AJNR Am J Neuroradiol 2016 Jun;37(6):1127–1131. Disclosures: S. Roychowdhury: 2; C; Stryker Neurovascular. 5; C; Surpass Streamline Proctor for Stryker Neurovascular. I. Kane: None. A. Saifuddin: None. P. Khandelwal: 3; C; Honoraria speaker for American Academy of Cardiology. E. Nourallah-Zadeh: None. G. Gupta: None.